Prosper : create the life you really want : six practices to find lasting money and happiness - Willis, Ethan (BK life book., 2011)
What is true prosperity? Is it simply having enough money? Certainly financial security is necessary for peace of mind. But for many people the pursuit of money stresses and exhausts them so much, it makes peace of mind impossible. And they?re always chasing after more?they never feel like they have enough. True prosperity is when there is no conflict between money and happiness?when you don?t have to drag yourself out of bed every morning because the way you make a living is true to who you are. And when your way of life is sustainable, you don?t fall victim to the boom/crash syndrome that afflicts so many people because you know exactly what you need to be happy and have a plan to achieve it. For the past twelve years Ethan Willis and Randy Garn have helped tens of thousands of people find their own personal path to prosperity. After nearly 11 million hours of personal coaching observation in eighty countries, they?ve developed six Prosperity Practices that will enable you to create a life that is rich, rewarding, and renewing. You begin by focusing on what you have, not on what you do not?you?ll be sur- prised what you find once you shift your way of thinking. A key part of this process is determining what Willis and Garn call your?Polaris Point?: a precise description of the life you want and what you need to sustain it. This becomes your own private North Star, guiding all your actions and keeping you from chasing after things you don?t really want or need. Then you?ll discover how to leverage your passions, experi- ence, and expertise to generate the income you require to reach your Polaris Point. Although you?ll find much to reflect on here, Prosper is an action guide?at the end of each chapter, Willis and Garn provide concrete steps you can take to make each of the Prosperity Practices a reality. Soon your life will be aligned with the core of your being, you will have a deep understanding of what you need to be happy, and you?ll know how to hold to that vision?and you will truly prosper.